Epidemiology of breast cancer in families in Iceland. Issue 3 (March 1992) - Tulinius, H; Sigvaldason, H; Olafsdóttir, G; Tryggvadóttir, L
Abstract : The Icelandic Cancer Registry has collected 989 pedigrees of breast cancer patients since 1972. In addition to the probands, the families also include 401 other women with breast cancer, so family information exists for 1390 women with breast cancer out of a total of 2748 diagnosed with the disease from 1910 to 1988. Most of the probands have been selected with care to avoid the bias of selecting families with a known history of breast cancer. After excluding all those who did not conform to the strict selection criteria, 947 pedigrees remained for this analysis. First, second, and third degree relatives all had a significantly increased risk of breast cancer: 2.26, 1.43, and 1.49, respectively. Male relatives also had a significantly increased risk, whereas females related by marriage had not. Of the first degree relatives, sisters had the largest increase in risk. When pedigrees were classified by the age at diagnosis of breast cancer of the proband, the risk was highest in the relatives of probands who were young at diagnosis. Bilaterality of breast cancer increased the risk in relatives and the highest risk (9.04) was found in sisters of probands with bilateral disease and an age at diagnosis of first cancer of less than 45 years (95% confidence limits 4.14, 17.18). Sisters consistently have the highest risk, significantly higher than other first degree relatives. This points to an important role of shared environmental aetiological factors acting after birth and it can not yet be excluded that most of the increase in risk can be explained by this.(ABSTRACT TRUNCATED AT 250 WORDS)